Intra-Attack Vestibuloocular Reflex Changes in Ménière’s Disease - Dario A. Yacovino; John B. Finlay (Case Reports in Otolaryngology)
Ménière’s attack has been shown to temporarily alter the vestibuloocular reflex (VOR). A patient with unilateral Ménière’s disease was serially evaluated with the video Head Impulse Test during single, untreated episodes of acute vertigo. Spontaneous nystagmus activity was concurrently recorded in order to establish the three typical phases of Ménière’s attack (irritative, paralytic, and recovery) and correlate them with VOR performance. The onset of attack was associated with a quick change in VOR gain on the side of the affected ear. While a rapidly progressive reduction of the VOR was evident at the paralytic nystagmus phase, in the recovery phase the VOR gain returned to normal and the direction of the previous nystagmus reversed. The membrane rupture potassium intoxication theory provides a good foundation with which to explain these dynamic VOR changes and the observed triphasic direction behavior of the spontaneous nystagmus. We additionally postulated that endolymphatic fluid displacement could have a synergic effect during the earliest phase of attack.